Work Posture Analysis and Potential Ergonomic Hazards Evaluation: Case at PT Pertamina Patra Niaga RJBT 4 Semarang - Lintang Ayu Karisma Dewi; M. Mujiya Ulkhaq (Journal of Psychology and Social Sciences, 2025)
PT Pertamina Patra Niaga Region Central Java (RJBT) 4 is responsible for monitoring, inspecting, and reviewing operations across Central Java and DIY. Among its functions, the health, safety, security, and environment (HSSE) team primarily conduct activities that require prolonged computer use, resulting in workers maintaining static postures for 8 hours a day, 5 days a week—posing a risk for musculoskeletal disorders (MSDs). This study analyzed workers’ postures and ergonomic risks using the rapid office strain assessment (ROSA), quick exposure check (QEC), and Indonesian National Standard (SNI) 9011:2021. Results showed that 10 out of 11 workers scored 6 on ROSA, and one scored 7, while 9 workers were classified at action level 3 and 2 at level 4 according to QEC. Based on these findings, recommendations include improving work postures per SNI 9011:2021 and Ministry of Health Regulation No. 48 of 2016, upgrading workstations with ergonomic chairs, footrests, and mouse pads, and fostering healthy habits aligned with Ministry of Health and Ministry of Manpower regulations. Additionally, implementing educational interventions such as awareness posters is suggested to enhance office ergonomics, promoting worker safety and comfort.